Penggunaan SIG untuk Pemetaan dan Analisis Jumlah Sebaran mahasiswa dan Perguruan Tinggi di Kabupaten Brebes - Bakhtiar, Tegar Robi; Bambang Agus Herlambang; Ahmad Khoirul Anam (JURNAL ILMIAH RESEARCH STUDENT, 2024)
Abstrak. The use of Geographic Information Systems (GIS) in mapping and analyzing the distribution of students and universities in Brebes Regency is an important need in educational development. This research aims to utilize the advantages of GIS in describing the spatial distribution of students and universities, as well as to carry out analysis related to geographic and demographic aspects. This research methodology involves collecting spatial and non-spatial data sourced from brebeskab.go.id. The data was then analyzed and modeled using Quantum Gis software, creating thematic maps that visualize the distribution of students and universities using spatial data. The research results show that GIS can provide a deeper understanding of the distribution of students and the location of universities. This analysis not only includes spatial aspects, but also involves demographic analysis to understand the characteristics of student distribution in each sub-district. The use of GIS in mapping and analyzing the distribution of students and universities provides valuable information for better decision making for local governments to develop education in the region.